Nature-Positive Seed Production for Sustainable Community Seed Banks in Kenya - Niane, Abdoul Aziz; Kemal, Seid Ahmed; Bishaw, Zewdie; Nyambok, Anne; Otieno, Gloria; Aluso, Lilian; Termote, Celine (2025)
Access to high-quality and affordable seeds is crucial for farmers to improve their yields, produce better quality crops, and enhance nutritional value. This is especially important for farmer-preferred cultivars, which are often open-pollinated varieties lacking systematic quality assurance support from the formal seed sector. Recognizing this need, the ICARDA-ALIANCE seed component, under Work Package 2 of the Nature-Positive Solutions-CGIAR initiative, focused on source seed production. This effort aims to support the multiplication and distribution of these valuable cultivars through Community Seed Banks (CSBs). Early generation seed production is a critical skill for Community Seed Banks (CSBs) aiming to scale their impact. Mastery of these techniques allows for increased seed multiplication and distribution, directly supporting large-scale crop production. This strengthens CSB sustainability and contributes to agrobiodiversity conservation, resilient food systems, and improved farmer livelihoods